A grammar of Gan Chinese : the Yichun language - Li, XuPing (Boston ; Berlin : De Gruyer Mouton, 2018)
China is very rich in language resources, and Mandarin is undoubtedly its most prestigious and well-known representative. Unfortunately, most of these languages remain understudied or even unstudied. Such is the case of Yichun Gan. Written in the style of a reference grammar, this book sets out to give a comprehensive and systematic description of Yichun grammar, with the aim of increasing readers' knowledge about Chinese languages other than Mandarin. In addition to common categories like nouns, verbs, adjectives and prepositions, the volume attempts to cover as many grammatical categories and constructions as possible, including the Sinitic-specific categories such as classifiers, the aspect system, postpositions and the object-marking BA constructions. To highlight its uniqueness, the book adopts a comparative perspective to contrast many features of Yichun Gan with Mandarin and other Sinitic languages. Our study shows that Yichun Gan possesses both Northern and Southern Chinese traits in many constructions, which supports its status as a transitional language. It will be of interest to linguists who wish to learn more about East Asian languages, and more specifically Sinitic languages.
Frontmatter -- Acknowledgements -- Preface -- List of abbreviations -- Contents -- 1. Gan and the Gan People -- 2. The Yichun sound system -- 3. Morphology -- 4. Personal pronouns -- 5. Possessives -- 6. Demonstratives -- 7. Numerals and classifiers -- 8. Adjectives and adjective phrases -- 9. Prepositions -- 10. Postpositions -- 11. Aspectuality -- 12. Modality -- 13. Negation -- 14. Resultative constructions -- 15. Ditransitives -- 16. BA constructions -- 17. Passives and causatives -- 18. Topic and focus related constructions -- 19. Relative clauses -- 20. Interrogatives -- 21. Clause linking: coordination and subordination -- References -- Index -- Appendix.
Includes bibliographical references (pages 293-298) and index.
eBooks on EBSCOhost
Keywords: Gan dialects (China) -- Grammar; Chinese language -- Dialects -- Grammar; Chinois (Langue) -- Dialectes -- Grammaire; FOREIGN LANGUAGE STUDY -- Southeast Asian Languages; Chinese language -- Dialects -- Grammar